2016
DOI: 10.1007/978-3-658-11490-9_17
|View full text |Cite
|
Sign up to set email alerts
|

The Biodemography of Fertility: A Review and Future Research Frontiers

Abstract: The social sciences have been reticent to integrate a biodemographic approach to the study of fertility choice and behaviour, resulting in theories and findings that are largely socially-deterministic. The aim of this paper is to first reflect on reasons for this lack of integration, provide a review of previous examinations, take stock of what we have learned until now and propose future research frontiers. We review the early foundations of proximate determinants followed by behavioural genetic (family and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 83 publications
(152 reference statements)
0
17
0
Order By: Relevance
“…Our findings are of interest to scientists within the medical, biological and social sciences alike [1,2,36,37]. Research has successfully identified genetic variants associated with reproductive diseases and traits [37].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Our findings are of interest to scientists within the medical, biological and social sciences alike [1,2,36,37]. Research has successfully identified genetic variants associated with reproductive diseases and traits [37].…”
Section: Discussionmentioning
confidence: 97%
“…Second, they imply that lower heritability estimates from GWAS studies compared to GREML approaches or family studies might be due to the fact that genetic effects are (to some extent) not universal but context specific. In the model considering gene-environment interaction across population and demographic cohort, we report heritability findings of 0.22 for NEB and 0.19 for AFB (see Fig 2 and S4 Table), which are fourfold higher than across all contexts and approach heritability estimates from family models [2,14]. It is therefore central to understand the cultural and environmental factors that interact with human fertility as well as their origins across (family) environments in order, for example, to define missing heritability or validate the findings from twin studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations